Dry Cough: A Major Limitation with Angiotensin Converting Enzyme Inhibitors in Nepalese Population - Rawat, Bharat; Sodhi, HS; Dhakal, Saroj; Shrestha, Bishwo kumar; Shah, Deepa; Bhusal, LAxman (Nepalese Heart Journal, 2008)
With the growing indications, Angiotensin Converting Enzyme Inhibitors (ACE- l) has become one of the most commonly prescribed medications in the clinical cardiology, Dry hacking cough or persistent throat irritation is one of the known side effects, which is possibly more common in the Himalayan kingdom of Nepal.